Bicyclol Alleviates Signs of BDL-Induced Cholestasis by Regulating Bile Acids and Autophagy-Mediated HMGB1/p62/Nrf2 Pathway - Zhao, Jingwen; Ran, Maojuan; Yang, Ting; Chen, Liwei; Ji, Peixu; Xu, Xiuxiu; Zhang, Lu; Sun, Siyuan; Liu, Xin; Zhou, Simin; Zhou, Lu; Zhang, Jie (Frontiers in Pharmacology, 2021)
Cholestasis is a liver disease characterized by the accumulation of toxic bile salts, bilirubin, and cholesterol, resulting in hepatocellular damage. Recent findings have revealed several key steps of cholestasis liver injury including the toxicity of bile acids and accumulation of proinflammatory mediator. In this study, we investigated the protective effect of bicyclol in cholestasis caused by bile duct ligation (BDL), as well as relevant mechanisms. Bicyclol attenuated liver damage in BDL mice by increasing the levels of hydrophilic bile acid such as α-MCA and β-MCA, regulating bile acid-related pathways and improving histopathological indexes. High-mobility group box 1 (HMGB1) is an extracellular damage-associated molecular pattern molecule which can be used as biomarkers of cells and host defense. Bicyclol treatment decreased extracellular release of HMGB1. In addition, HMGB1 is also involved in regulating autophagy in response to oxidative stress. Bicyclol promoted the lipidation of LC3 (microtubule-associated protein 1 light chain 3)-Ⅱ to activate autophagy. The nuclear factor, E2-related factor 2 (Nrf2) and its antioxidant downstream genes were also activated. Our results indicate that bicyclol is a promising therapeutic strategy for cholestasis by regulating the bile acids and autophagy-mediated HMGB1/p62/Nrf2 pathway.